Some Problems Concerning the Bulgaria’s Adaptation to EU Common Trade Policy - Hadzhinikolov, Dimitar (Research Papers, 2010)
Bulgaria could achieve its economic and trade goals with a greater success by better using the tools of the EU Common trade policy. To do that Bulgaria has to change its exports commodity structure and to make it similar to the commodity structure of EU exports. At present time there are significant differences between these both structures. In Bulgaria’s exports dominate resources intensive and labor intensive goods and in EU exports dominate capital intensive and knowledge intensive goods. Significant differences exist also in the geographical distribution of trade. Important EU trade partners as USA, China, Japan, Brazil, Canada, play a quite limited role in Bulgaria’s foreign trade. There is also an unused capacity for development of the trade between Bulgaria and a number of African countries, which used to be in friendly relationship with Bulgaria in the recent past and are now under a special preferential tariff regime in their trade with EU.